Hubungan Body Image dengan Self Esteem pada Siswa SMA dan Implikasinya dalam Pelayanan Konseling - Fani, Salsa Billa Dwi; Nurfarhanah, Nurfarhanah (Lembaga Yasin AlSys, 2024)
This research is motivated by students who have low self-esteem because students feel they have a negative body image. Students tend to be dissatisfied with their body shape, and even consider physical condition to be a mandatory standard that other people pay attention to. This research aims to describe body image and self-esteem in students and their implications for counseling services. This type of research uses a quantitative approach with descriptive methods. The population of this study was 694 students of SMAN 1 2x11 Enam Lingkung who were registered in the 2024/2025 academic year, the sample for this study was 328. Sample selection used proportional random sampling technique. The data collection technique uses a scale for body image and self-esteem. Data were analyzed using descriptive techniques. The research results show that overall body image is in the medium category, while overall self-esteem is in the high category. Services that can be provided to students to improve body image and self-esteem include information services and group guidance services.